Do Infants Really Experience Emotional Contagion?. (2nd August 2017) - Ruffman, Ted; Lorimer, Benjamin; Scarf, Damian
Abstract: Several modern theories on the origins of human empathy and morality hold that empathic understanding is innate and use research on emotional contagion to support this claim. However, all studies on emotional contagion are limited and far from conclusive. In this article, we argue that the findings from these studies could be explained alternatively in terms of neonates responding to nonemotional acoustic features of the cries they hear rather than to the emotional distress the cries convey. We highlight several areas of concern in the literature and show how research findings on emotional contagion fit comfortably within the alternative framework of acoustic features. Beyond its implications for the literature on emotional contagion, the questions we raise have implications for theories on the origins of morality and empathic understanding. Given the recent proliferation of these theories, this highlights the need to examine with greater scrutiny the evidence that supports them, particularly studies on emotional contagion.